Internalization of Religious Teachings on the Aspects of Honesty and Discipline in Child-Friendly Elementary Schools - Keiko Ayu Safitri; Wahdan Najib Habiby (Elementary Teacher Education Program, Majalengka University, 2025)
Aspects of honesty and discipline are important parts of character that must be built. However, in schools, the value of honesty and discipline is still problematic and needs to be studied more deeply, especially in elementary schools. The purpose of the research is to look at and create a pattern of internalization of religious teachings that can be used as a consideration in instilling honesty and discipline in elementary schools. This internalization pattern includes the stages of instilling honesty and discipline in schools. This research is qualitative research with a phenomenological method. Data collection techniques through interviews, questionnaires, documentation, and observations. Research shows that in the context of Religious Education, the cultivation of honesty and discipline is part of Religious Teachings, with the habit of students getting used to behaving better, such as saying greetings, worshipping on time, and imitating the commendable attitude of the Prophet. Students have implemented this aspect in their daily lives, especially in the school environment. This can be seen from the honesty of grades IV and V, which obtained good category results with a percentage of 68% and 72%. Meanwhile, discipline obtained good category results with the same percentage, as much as 68%.